1996
DOI: 10.1037/0735-7044.110.4.746
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory thalamus lesions in the rat: II. Aversive and appetitive taste conditioning.

Abstract: The learning capacities of rats with electrolytic lesions of the gustatory thalamus (GT) were investigated in 3 experiments. In Experiment 1, the presence of a taste cue failed to overshadow odor aversion learning in the lesioned rats, yet these same animals acquired normal taste and odor aversions. Thalamic lesions had no discernible effect on the acquisition of a conditioned flavor preference in Experiment 2. Finally, GT lesions completely reversed the anticipatory contrast effect shown by control subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 58 publications
5
75
0
Order By: Relevance
“…Early research favored a role for the GT in CTA acquisition (e.g., Lasiter, 1985;Loullis, Wayner, & Jolicoeur, 1978;Yamamoto, 1993;Yamamoto & Fujimoto, 1991;Yamamoto et al 1995). However, more recent research, using electrolytic lesions that caused minimal damage beyond the boundaries of the GT, finds no evidence that discrete GT lesions disrupt first-order CTA (e.g., Flynn, Grill, Schulkin, & Norgren, 1991;Grigson, Lyuboslavsky, & Tanase, 2000;Reilly & Pritchard, 1996). Although ibotenic acid GT lesions do disrupt CTA acquisition when multiple CSs are involved (Reilly, Bornovalova, Dengler, & Trifunovic, 2003), the deficit cannot be interpreted as a disruption in the processing of US-related information.…”
Section: Discussionmentioning
confidence: 99%
“…Early research favored a role for the GT in CTA acquisition (e.g., Lasiter, 1985;Loullis, Wayner, & Jolicoeur, 1978;Yamamoto, 1993;Yamamoto & Fujimoto, 1991;Yamamoto et al 1995). However, more recent research, using electrolytic lesions that caused minimal damage beyond the boundaries of the GT, finds no evidence that discrete GT lesions disrupt first-order CTA (e.g., Flynn, Grill, Schulkin, & Norgren, 1991;Grigson, Lyuboslavsky, & Tanase, 2000;Reilly & Pritchard, 1996). Although ibotenic acid GT lesions do disrupt CTA acquisition when multiple CSs are involved (Reilly, Bornovalova, Dengler, & Trifunovic, 2003), the deficit cannot be interpreted as a disruption in the processing of US-related information.…”
Section: Discussionmentioning
confidence: 99%
“…The suppressive effects of cocaine and sucrose, but not LiCl, are augmented in rats with a history of chronic morphine treatment [57]. Finally, bilateral lesions of the gustatory thalamus or gustatory cortex disrupt the suppressive effects of morphine, cocaine, and sucrose, but have no impact on the development of a LiCl-induced CTA [58][59][60][61][62][63][64][65]. Taken together, the data confirm that drug-induced suppression of CS intake is not mediated by a conditioned taste aversion like that induced by the aversive agent.…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 99%
“…Some studies have reported that VPMpc-lesioned animals retain a normal concentration response to preferred and non-preferred tastes [134][135][136][137] but may have disrupted [137], impaired [127,130] or else have no effects on CTA [134,135,138,139]. Current views suggest a role in comparing novel and familiar tastes [140] in more complex gustatory learning tasks or in attention to gustatory function [135,136,141].…”
Section: The Gustatory System In the Ratmentioning
confidence: 99%